Evaluation of bulk and surfaces absorption edge energy of sol-gel-dip-coating SnO2 thin films - Floriano,Emerson Aparecido (2010)
The absorption edge and the bandgap transition of sol-gel-dip-coating SnO2 thin films, deposited on quartz substrates, are evaluated from optical absorption data and temperature dependent photoconductivity spectra. Structural properties of these films help the interpretation of bandgap transition nature, since the obtained nanosized dimensions of crystallites are determinant on dominant growth direction and, thus, absorption energy. Electronic properties of the bulk and (110) and (101) surfaces are also presented, calculated by means of density functional theory applied to periodic calculations at B3LYP hybrid functional level. Experimentally obtained absorption edge is compared to the calculated energy band diagrams of bulk and (110) and (101) surfaces. The overall calculated electronic properties in conjunction with structural and electro-optical experimental data suggest that the nature of the bandgap transition is related to a combined effect of bulk and (101) surface, which presents direct bandgap transition.